Language, multimodal interaction and transaction studies of a southern Chinese marketplace - Xiang, Xuehua, 1976- (Studies in Chinese language and discourse ;, 2021)
"Xuehua Xiang examines multimodal interaction in the marketplace in a multilingual town at the juncture of urbanization in Southern China. Using a collection of data that span nearly 20 years from ethnographic fieldwork, Language, Multimodal Interaction and Transaction: Studies of a Southern Chinese marketplace analyzes multimodal talk-in-interaction in the traditional marketplace as both an economic mechanism and a localized social space. Focusing on how buyers and sellers interact to complete transactions as marketplace shifts from sedimentations of road-side peddling to centralized built space and further to corporate e-commerce, Xiang takes into account the Janus nature of language as both incurring transaction costs and a powerful tool of information and control. By analyzing the socializing functions of language in the marketplace outside of and beyond economic dealings, the study additionally documents and depicts the roles of affect and morality in marketplace encounters. The study offers an overarching framework for future research on the mediating role of language and multimodal interaction in economic activities as well as on the interplay of information, knowledge, affect and morality in social encounters"--